Analysis and Simulation of Mathematical Model of COVID-19 Incorporated with Vaccination and Media Induced Fear - Bashiru, Kehinde Adekunle; Kolawole, Mutairu Kayode; Olaosebikan, Mutiu Lawal (Trends in Sciences, 2023)
COVID-19 pandemic is now increasing concern to authorities and public health officials. The study is aimed to investigate the impact of vaccination in the absence of media induced fear. In this research, analysis and simulation of a mathematical model of COVID-19 incorporated with media induced fear and vaccination was made, the total population is divided into 5 sub-population classes; Susceptible, Exposed, Infected, Quarantine and Recovery. The disease free and the endemic equilibrium of the model were carried out and the basic reproduction number was obtained using the next generation matrix. The stability analysis of the model was done and it was ascertained that the disease free equilibrium of the biological model is stable. Due to its efficiency and accuracy in handling nonlinear coupled ordinary differential equations, the homotopy perturbation method is applied to obtain the approximate solution of the mathematical model and the obtained results was simulated using the computation software Maple 18 to study the impact of vaccination in each compartment of the model when the media induced fear. The outcome of the simulation process were presented graphically and interpreted accordingly and it was discovered that in eradicating the spread of COVID-19 in a society where there is no fear, vaccination is an alternative and better measure. HIGHLIGHTS Model formulation with vaccination Stability analysis of the disease free equilibrium and endemic equilibrium Numerical simulation of the mathematical model using the homotopy perturbation method Analysis of the impact of vaccination in controlling the spread of COVID-19 in the absence of media induced fear GRAPHICAL ABSTRACT